2021
DOI: 10.1021/acs.jpcc.1c07386
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Electronic Structure and Electrochemical Properties of Na2MnSiO4 as a Cathode Material for Na Ion Batteries

Abstract: The polyanionic compound Na 2 MnSiO 4 is regarded as one of the promising cathode materials for Na ion batteries due to good specific capacity with its attractive prospect of utilization of two electrons in the redox processes. Therefore, in this study, we have performed the thermodynamic and electronic structure analysis of Na 2 MnSiO 4 using first-principles density functional theory calculations. The intermediate ground state configurations for Na 2 MnSiO 4 of Na deintercalation were found by using the clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 64 publications
2
8
0
Order By: Relevance
“…The COHP results demonstrate that remarkable bonding states closely below Fermi level appear due to the presence of CuO bond. [ 47 ] According to previous reports, the bonding states should be related to the π‐type interactions between nonbonding O 2p and Cu t 2g states as a consequence of strong CuO covalency. [ 48 ] Therefore, the nonbonding O 2p states are effectively stabilized by the neighboring Cu elements owing to the presence of π‐type interactions, in good accordance with the DOS results.…”
Section: Resultsmentioning
confidence: 95%
“…The COHP results demonstrate that remarkable bonding states closely below Fermi level appear due to the presence of CuO bond. [ 47 ] According to previous reports, the bonding states should be related to the π‐type interactions between nonbonding O 2p and Cu t 2g states as a consequence of strong CuO covalency. [ 48 ] Therefore, the nonbonding O 2p states are effectively stabilized by the neighboring Cu elements owing to the presence of π‐type interactions, in good accordance with the DOS results.…”
Section: Resultsmentioning
confidence: 95%
“…Although no experimental observation of Na ion/vacancy ordered structures have been reported for other sodium metal silicates, including Na 2 FeSiO 4 , , and Na 2 MnSiO 4 , a recent DFT study of the isostructural Na 2 MnSiO 4 has identified a stable intermediate phase for Na 1.5 MnSiO 4 . We note that most experimental studies of transition metal silicates used nanoparticles for improved rate capability, 107 yet the size broadening of the Bragg peaks may have smeared the weak satellite reflections, which makes them difficult, if not impossible, to measure by powder diffraction method.…”
Section: Resultsmentioning
confidence: 76%
“…and the Na + /vacancy ordering, the mechanism of which accounts for the superstructure of Na 0.7 FePO 4 . 39,42 The observation of Na + /vacancy ordering by X-ray diffraction has been well documented in previous X-ray diffraction studies of Na + /vacancy ordered structures, 34,39,41,42 45 We note that most experimental studies of transition metal silicates used nanoparticles for improved rate capability, 107 yet the size broadening of the Bragg peaks may have smeared the weak satellite reflections, which makes them difficult, if not impossible, to measure by powder diffraction method. In contrast, the micrometer-sized Na 2 CoSiO 4 particles used in the present work do not suffer from size broadening, and sharp satellite reflections are readily captured by powder diffraction.…”
Section: ■ Results and Discussionmentioning
confidence: 78%
“…The slope of the convex hull is directly related to the average voltage. 99 As shown in Fig. 8(a) and (c), when the concentration x = 0.2, none of the structures falls on the convex hull indicating that none of them are stable at 0 K. Along with DFT ground states, multiple metastable states fall just above the convex hull in most of the intermediate Li concentrations in all the systems, as shown in Fig.…”
Section: Li-ion Diffusion In LImentioning
confidence: 70%
“…The total energy of the O 2 molecule is calculated from the more accurate total energies of H 2 O and H 2 from calculations using the supercell approach, as mentioned elsewhere. 99 The calculated oxygen release energy as a function of delithiation in Li y Fe (1− x ) Co x O 4 is plotted in Fig. 10.…”
Section: Resultsmentioning
confidence: 99%